Layered Metamaterial Beam Structures With Local Resonators for Vibration Attenuation: Model and Experiment - Anigbogu, Winner; Nguyen, Hieu; Bardaweel, Hamzeh (Frontiers in Mechanical Engineering, 2021)
Layered metamaterial beam structures are gaining increased attention in a variety of fields including vibration attenuation and energy harvesting. Exhaustive research on single-beam metamaterial vibration attenuation structures using local resonators exists in literature. Moreover, there are recent attempts at modelling double-layered beams with different kinds of constraints. The double-layered beam models in literature are limited to simple beams and not extended to metamaterials with local resonators. This article is focused on developing a design criteria and modelling platform for layered metamaterial beams with local resonators for vibration isolation. The model is developed using Euler-Bernoulli beam equations, superposition of mode shapes and Galerkin methods. A prototype layered metamaterial structure is fabricated and characterized experimentally. The prototype consists of horizontal beams, local resonators forming unit cells, and vertical beams linkages. Each local resonator consists of cantilevers with tip masses. Results show good agreement between model and experiment. Two major bandgaps are observed at 190 Hz – 410 Hz and 550 Hz – 710 Hz. Results reveal that the low frequency bandgap can be further reduced through the design of the local resonators. Results also show that alternating the length of the local resonators causes a shift in the first frequency bandgap. An increase in the number of local resonators opens up extra frequency bandgaps at lower frequencies with the drawback of reducing the depth in vibration transmissibility. Moreover, the higher frequency bandgaps are mostly affected by the horizontal beams. An increase in the length of the horizontal beams, while the number and design of the local resonators are fixed, broadens the second frequency bandgap and shifts it to lower values.